Ushul Tafsir and Qawaid Tafsir Nusantara: A Review Of Nawawi Al Bantani's Book Of Tafsir Marah Labid - Erlan Dwi Cahyo; Andri Nirwana (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2022)
Tafsir is an effort to understand the Quran to find out the meaning and content of the verses of the Quran It is a result of human labor (it is different from the Quran) that has developed and changed from classical period to contemporary. It is diverse in terms of methods (manhaj/tariqah), patterns (nau'), and approaches (alwan). The book of Tafsir Marah Labid or Tafsir Al Munir written by Syekh Nawawi Al-Bantani is considered an interpretation that connects between traditional times and modern times. It is different from other tafsir in Archepelago because it uses Arabic, of which was novel in Nusantara’s works during the time. Other than that, Tafsir Marah Labid also contains some of the teachings that represent its time when Dutch colonialist colonized Nusantara.